An Adaptive Isogeometric Phase‐Field Model for Topology Optimization. Issue 1 (25th January 2021) - Hennig, Paul; Heindel, Leonhard; Kästner, Markus
Abstract: In this contribution, we apply adaptive isogeometric analysis to a phase‐field model for topology optimization. To increase the efficiency of the computation, we perform local mesh refinement and coarsening between the time increments of the simulation. To provide a trial solution for the iterative solver of the next increment, state variables are projected from the old to the new mesh. The quality and efficiency of the approach are tested in a two‐dimensional benchmark.